A interdisciplinaridade como princípio norteador da pesquisa em ciências ambientais - Correia, Sofia Oliveira de Barros (2015)
This research aimed to analyze the use and / or the employ of the word interdisciplinarity carried out by graduate students of the Graduate Program in Development and Environment of the Federal University of Sergipe in the last 12 years ( 2003-2014 ) . The study focus on the analysis of theoretical elements, methodological and / or paradigm corresponding to the interdisciplinarity notion present in dissertations. Two hundred and forty-nine dissertations were analyzed. It adopted the discursive approach Pêcheux, French Discourse Analysis (ADF), for the analysis and processing of information . The interaction in the research took place from participating actively, in the sense that the author is located in socio- historical reality studied. The main results of the research explain that interdisciplinarity is taken consensually as a guiding principle; this approach is presented in the interdisciplinary training of research, course design, the interaction in the classroom, in management meetings and field work carried out by coordination, staff, teachers and students. However, in dissertations, employ and / or the use of the term interdisciplinarity shows five major characteristics: a) there are differences in the concept of the management of research (confusion content); b) is predominant theoretical dimension of interdisciplinarity (cognitive consensus); c) there is no specific methodological design to interdisciplinarity (pragmatic nullity); d) there is adoption of sustainability as a matrix, reference and / or index the interdisciplinary analysis (instrumental inversion); e) elects to interdisciplinarity as a criterion for measuring learning. We conclude that the use and / or the employ of interdisciplinarity are restricted to the theoretical dimension and are associated with the evaluation process of academic education. This reduction obscures the identification of methodological aspects, suitable to characterize and justify the relevance of interdisciplinarity in carrying out the dissertations analyzed.